New Civilization in the Post-Covid-19 Health World & Lesson Learned from the Netherlands - Armyn Nurdin; Tjay Tan; Isti Ilmiati Fujiati (Faculty of Medicine, Public Health, and Nursing, 2020)
New Civilizations in the Post-Covid-19 World Health There are several possibilities that will happen after the Covid-19 outbreak ends. This is the other side of the Covid-19 pandemic. There is a term called see the un- seen, or seeing something before it happens. An illustrative example is that everyone sees the apple falling down, but only one person sees why or what causes the apple to fall down. This is Isaac Newton. Based on this phenomenon, the formula for the gravitational force or the gravitational force of the earth is triggered. This paper focuses on what might happen in the future.Indeed, the earth repairs itself in its own way, and that is for the benefit of mankind. The Covid-19 outbreak that is currently happening is a very positive thing for human life. Under the earth there are shifts in the earth’s plates which cause tectonic earthquakes. What is the goal? The aim is to stabilize the earth so that an asteroid collision does not occur. There is a plague on earth, what does it mean? Its meaning is to improve human life. So, let’s interpret the current outbreak as something positive. Previously in Europe, there were millions of deaths due to PES disease. At that time, most farmers died, so the land owners were short of labor. What is the meaning? First, farmers have a high bargaining position. Second, after the plague occurred, then there was the collapse of feudalism. In the past, peasants worked in a kind of forced labor. Then the modern economic system was born. It was started at that time when farmers were paid in cash which had never happened before. This was the beginning of the growth of the modern economic system2.